From Proprietary Textbook to Custom OER Solution: Using Learner Feedback to Guide Design and Development - Dennen, Vanessa P.; Bagdy, Lauren M. (Online Learning, 2019)
This study presents the initial needs analysis and formative evaluation of the beta version of an open educational resource (OER) textbook solution. The OER textbook, created by the authors, replaces a proprietary, paper-based textbook and is delivered to students digitally, within a learning management system. Findings show that students are concerned about cost and convenience, and are likely to seek course content online before reading material in traditional course textbook. Many do not purchase assigned textbooks at all. Students also want mobile access to course readings, and for those readings to be brief and targeted, covering just the necessary content for completing coursework. Students provided positive feedback on the OER textbook, indicating that it helped them meet course learning objectives. The online integration of reading and other content materials within the LMS encouraged use. Students reported higher rates of access and appreciation that it was free. These findings suggest that instructors should consider the cost, format, length, and relevance of assigned readings in courses, whether they are ready to adopt, adapt or create open digital textbooks or continue to use proprietary, paper-based ones.